The Reality of Implementing Voluntary Hours in the Tracks System in Secondary Schools in the Northern Border Region from the Students’ Perspective and Its Impact on Their Career Maturity - Alshammary, Talal Glub; Abanmi, Fahd AbdulAziz (Journal of Curriculum and Teaching Methodology, 2025)
The current study aimed to identify the reality of implementing volunteer hours in high schools from the perspective of high school students in the Northern Borders region and its impact on their professional maturity in general education. The study population consisted of 900 male high school students, with a sample of 230 students from general education high schools in the Northern Borders region. The results indicated that the reality of volunteer hours among high school students was rated highly, and the impact of these volunteer hours on students' professional maturity was also rated highly. The findings showed no statistically significant differences at the significance level (α < 0.05) regarding the reality of implementing volunteer hours and their impact on professional maturity attributed to the variable of study stage. However, there were statistically significant differences at the significance level (α < 0.05) regarding the reality of implementing volunteer hours and their impact on professional maturity attributed to the volunteer track, favoring the technical and religious tracks. Based on the results, the study recommended the necessity of developing and enhancing volunteer hour programs in high schools, focusing on diversifying volunteer tracks to meet students' various interests and increase their participation.
Keywords: Track System; Volunteer Hours; Secondary Education; Vision 2030